Structure and thermodynamics of Diol inclusion compounds - Schubert, Wolf-Dieter (University of Cape Town, 2015)
Includes bibliographical references. === This work is predominantly concerned with the structural analysis of the coordinatoclathrates formed by the host compound trans-9,10-dihydroxy-9,10-diphenyl- 9,10-dihydroanthracene (1) with compounds containing neutral nitrogen atoms (Lewis bases). The structures of inclusion compounds with two nitriles (acetonitrile and 3- hydroxypropionitrile), with pyridine and with three substituted pyridines (3- methylpyridine, 2,4-dimethylpyridine and 2,6-dimethylpyridine) have been solved by single crystal X-ray diffraction methods. The crystal packing modes and hydrogen bonding schemes have been elucidated, while the guest cavities have been investigated. The thermal stability of the complexes was analysed by thermogravimetric analyses and differential scanning calorimetry. These techniques were employed in determining the guest content, in investigating the thermal properties of the compounds and in establishing the activation energies for the desorption processes. Desorption studies, utilising X-ray powder diffraction, were used to investigate the structures resulting from the desorption of guest from the complexes. The selectivity of the host for either of the isomers 2,4- and 2,6-dimethylpyridine was investigated.